EFFECTIVENESS OF BLENDED LEARNING IN EDUCATION - Saydibragimova Yulduzxon; Madirimova Gulmira (Journals Park Publishing, 2024)
This article explores the effectiveness of blended learning in the realm of education, a dynamic approach that integrates traditional face-to-face instruction with digital resources and online activities. Examining the blend of tradition and technology, the article highlights the benefits of personalized learning, flexibility, and accessibility that come with this innovative pedagogical model. Enhanced engagement, coupled with the development of real-world skills, positions blended learning as a transformative force in preparing students for the challenges of the 21st-century workforce. However, the article also addresses challenges such as infrastructure requirements and the need for educator training. Through careful consideration and planning, blended learning stands poised to reshape the educational landscape, offering a dynamic and personalized learning experience for students, ultimately influencing the future of education.
Keywords: Blended learning, education, technology, personalized learning, flexibility, accessibility, engagement, real-world skills, challenges, considerations